2013
DOI: 10.3389/fphar.2013.00079
|View full text |Cite
|
Sign up to set email alerts
|

Alternative functional in vitro models of human intestinal epithelia

Abstract: Physiologically relevant sources of absorptive intestinal epithelial cells are crucial for human drug transport studies. Human adenocarcinoma-derived intestinal cell lines, such as Caco-2, offer conveniences of easy culture maintenance and scalability, but do not fully recapitulate in vivo intestinal phenotypes. Additional sources of renewable physiologically relevant human intestinal cells would provide a much needed tool for drug discovery and intestinal physiology. We compared two alternative sources of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 42 publications
3
75
2
Order By: Relevance
“…To our knowledge, there are few reports involving drug membrane permeability using human iPS-derived enterocytes (Kauffman et al, 2013;Ozawa et al, 2015). However, this evaluation used only TEER measurements and the permeability of a nonabsorbable marker (fluorescein isothiocyanate-dextran, molecular weight 4 or 150 kDa) in these reports.…”
Section: Intestinal Transport In Human Ips Cell-derived Enterocytes 1665mentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are few reports involving drug membrane permeability using human iPS-derived enterocytes (Kauffman et al, 2013;Ozawa et al, 2015). However, this evaluation used only TEER measurements and the permeability of a nonabsorbable marker (fluorescein isothiocyanate-dextran, molecular weight 4 or 150 kDa) in these reports.…”
Section: Intestinal Transport In Human Ips Cell-derived Enterocytes 1665mentioning
confidence: 99%
“…However, the pharmacokinetic functions of organoids and intestinal cells were only briefly explored in these studies. Kauffman et al (2013) and Ozawa et al (2015) have reported the pharmacokinetic characteristics of human iPS-derived enterocyte-like cells, but the characteristics of intestinal transport have been insufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Generation of more biologically-complex intestinal tissue has been accomplished through directed differentiation of (embryonic or induced) pluripotent stem cells to intestinal tissue (Kauffman et al, 2013;Ogaki et al, 2013). In general, pluripotent stem cells can be differentiated into all cells of the three embryonic germ layers.…”
Section: Co-culture and Pathophysiological Modelsmentioning
confidence: 99%
“…Directed differentiation of human embryonic stem cells and induced pluripotent stem cells (iPSC) to intestine-like organoids with crypt-villus physiology and long-term culturing capacity has been achieved (Sato et al, 2011). However, current schemes for human intestine stem cells frequently rely on 3D culture conditions, whereas monolayer cultures are required for absorption experiments (Kauffman et al, 2013). Protocols are currently being optimized to achieve this goal (Astashkina and Grainger, 2014).…”
Section: In Vitro Methods For Intestinal and Liver Metabolismmentioning
confidence: 99%